The dark side of batteries: Education, fertility and cobalt mining in the Democratic Republic of Congo - Maurizio Malpede (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2020)
Being rich of crucial minerals might be a leading determinant of local economic development. On the other hand, intensive extraction might prove to negatively affect the health and wealth of people living close to mineral deposits and the surrounding environment. I examine the effects that local cobalt mining had on child labor and subsequently on fertility rates in the DRC by exploiting geographic variation of cobalt deposits prior to the boom of modern electric batteries and using both education attainment and fertility data. I find that the boom in cobalt mining led to a reduction in educational achievements of individuals who were between 6 and 14 at the time of the boom, and it was accompanied by higher fertility rates. Moreover, the analysis shows an initial improvement in wealth of households exposed to cobalt mining which however, disappears after seven years. The results are robust to spatial spillover effects and selective migration.
Keywords: I25; J13; O13; 330; Schwermetall; Kinderarbeit; Schulbesuch; Fertilität; Räumliche Verteilung; Kongo (Demokratische Republik)